OCCURRENCE OF CANINE PARVOVIRAL GASTRO ENTERITIS IN AND AROUND BENGALURU - H.V. Sanjay; G.K. Chetan Kumar; G. Leena (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Canine parvoviral gastroenteritis is one of the most common viral diseases found in dogs and caused by canine parvovirus (CPV) type 2. Young dogs are highly susceptible to the disease with high morbidity and mortality. The present study was conducted at the Department of Veterinary Medicine, Veterinary College, Bengaluru to know the occurrence pattern of CPV infection among PCR positive dogs under one year of age presenting with signs of gastroenteritis. The occurrence of CPV infection was high in puppies less than three months old, non-descript, male, irregularly dewormed, unvaccinated dogs weighing between four andeight kilograms, acquired from breeding kennels and housed indoors in a multi-pet household. These epidemiologic patterns highlighted the need for timely vaccination, deworming and biosecurity measures to mitigate CPV burden and improve survival in puppies.